PENGARUH ASSESSMENT AS LEARNING TERHADAP EFIKASI DIRI PESERTA DIDIK PADA PEMBELAJARAN PENYUSUNAN LAPORAN KEUANGAN PERUSAHAAN DAGANG SMKN 1 SURAKARTA - Ramdhani Aigera Fajri; Sudiyanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of Assessment as Learning on students' self-efficacy in learning financial statement preparation for trading companies in Grade XI Accounting and Financial Institution Program at SMK Negeri 1 Surakarta. Based on by the low level of students' confidence in their ability to complete learning tasks. This research employed a quasi-experimental method using a non-equivalent control group design. The sample consisted of 29 students in the experimental class and 33 students in the control class. Data were collected through a self-efficacy questionnaire administered before and after the learning process. Data analysis was conducted using normality tests, homogeneity tests, independent sample t-test, and paired sample t-test. The results showed that the mean self-efficacy score of students in the experimental class increased from 42.45 to 47.10, while the mean score in the control class increased from 41.76 to 43.36. The independent sample t-test yielded a significance value of 0.018 (< 0.05), indicating a significant difference in self-efficacy between the two groups. Therefore, it can be concluded that the implementation of Assessment as Learning had a positive and significant effect on students' self-efficacy in learning the preparation of financial statements for trading companies at SMK Negeri 1 Surakarta.